CARPE: mapping Central African forest resources by satellite - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Deirdre Smith explains how the CARPE project is using satellite-derived maps to identify threatened Congo Basin forest areas.